PENGARUH PENYULUHAN IMUNISASI TERKINI PADA BAYI DAN BALITA TERHADAP PENGETAHUAN IBU DI DESA BRAJAN KABUPATEN SLEMAN YOGYAKARTA - Dian P, Grhasta; Fit A, Elvika (MEDIA ILMU KESEHATAN, 2015)
Background:Immunization has been proven as one effort of society health care which is very important. Based on preliminary reaserch conducted in Yogyakarta Special regency, immunization coverage data obtained during the year 2013 was reach the target of Renstra indicator, but it need 15% to be the perfect number of immunization. Factors that correlated to the completennes of primmary immunization include knowledge, motive, work experience, Family support, Posyandu (an integrated healthcare service centre) facilities, environment, attitude, healthcare provider, income and education. Due to the stated fact above, information about the update immunization need to be given to the women who has children under 5th years old by giving them an update immunization education. Objective:to find out the effect of an update immunization education to the women knowledge in the Brajan village. Methods: This study was quasi-experimental with one group pre-post test. The subject of this study was 46 women in Posyandu Brajan Village. The data were taken from the questionnaries of knowledge an update immunization. The data were analyzed by using paired t-test. Result: The result of the analysis were tstatistic=6.484 with df= 29, ttable=2,04 ;significant score (P) = 0,001. So, P score < 0,05 (0,001 < 0,05). This result meant that there was significant difference between pre and post education. Conclution: The writter concluded that an update immunization education affected positively to the woman knowledge. Key words: An update immunization, Knowledge, Education